Assessment of the essential attributes of Primary Health Care for children - Juliane Pagliari Araujo; Cláudia Silveira Viera; Beatriz Rosana Gonçalves de Oliveira; Maria Aparecida Gaiva; Rosa Maria Rodrigues (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To identify the presence and extent of essential attributes in primary health care services for children, focusing on the evaluation of structure and process. Method: Evaluative, quantitative study carried out in 23 traditional basic health units in a city in Parana State, with 548 caregivers of children under 12 years old, using the Primary Care Assessment Instrument (PCATool Brazil), child version. Essential and general scores of the primary care were calculated according to the methodology proposed, with a cut-off score ≥6.6. Results: The scores of the essential attributes in relation to structure are: Accessibility (5.5), Kinship (6.9), Integrality of care - Services Available (6.0) and Coordination - System information (7.4). As for the Process, the following results were obtained: First visit - Use (8.6), Longitudinally (6.1), Integrality - Services Provided (6.1) and Coordination - Integration of Care (6.9). Conclusion: The essential score was 6.6 and the general score was 6.3, showing weak focus on primary health care.